Performance Analysis of SF6 Circuit Breakers: Case Study of Rungkut 150 kV Main Substation - Reza Sarwo Widagdo; Puji Slamet; Fernanda Eka Saputra (LPPM Universitas PGRI Adi Buana Surabaya, 2024)
Electrical energy transmission plays an important role as a means of distributing electrical energy from generation to distribution and consumers. During the process of distributing electrical energy, disturbances such as short circuits often occur. Therefore, there needs to be safeguards so that the distribution process runs well. One of the safety equipment in the main substation is the circuit breaker. Circuit breaker is a mechanical switch or switching equipment that can close, transmit or disconnect the load current under normal conditions or under abnormal conditions such as a short circuit. Problems with circuit breaker can be detrimental and disrupt the operation of the electric power system. If the circuit breaker does not work properly when a disturbance occurs, the disturbance can damage other devices and cause instability in the distribution of electrical power. Therefore, regular testing and maintenance must be carried out to ensure the circuit breaker is suitable for operation. The testing stages include SF6 pressure, insulation resistance, contact resistance, and circuit breaker contact simultaneity. The test results show SF6 pressure with a value above the circuit breaker nameplate, insulation resistance with a value above 150 MΩ, contact resistance with a standard value below 50 µΩ, and contact simultaneity testing is carried out by calculating the delta time when close and open on each phase in below the value of 10 ms. In accordance with the results of SF6 gas pressure testing, insulation resistance, contact resistance and circuit breaker synchronization at the 150 KV Rungkut Bay Line Main Substation, Surabaya Selatan, it is in operational condition.